EFEKTIVITAS PENERAPAN KOMPILASI HUKUM ISLAM DALAM PENYELESAIAN PERKARA PERCERAIAN (STUDI DI PENGADILAN AGAMA DOMPU - Israfil, Israfil; Salat, Muzakir (Jurnal Ilmiah IKIP Mataram, 2019)
This research aims to examine the legal norms that are applicable in resolving divorce cases, then examine their application to judges' considerations in giving their decisions, and review the factors that cause the occurrence of case studies in Dompu Regency and how legal considerations are applied in decisions. the judges. So the data sources are documents and interviews with judges and communities who have experienced and are aware of the causes of legal incidents relating to household temptation between husband and wife in Dompu Regency, West Nusa Tenggara Province. The results of the study show that the number of students has increased from year to year since 2013, the number of 479 (17.91%), in 2014 there were 691 (25.85%), in 2015 the figure was 719 (26.89%), in 2016 the figure was 785 (29.35 %). This belief number consists of cereals of talak and cerei gugat. Whereas the causes of the investigation in the Dompu Religious Court were the affair factors which caused the couple to continue to quarrel so that the household could not be maintained, then the second factor was the husband and wife working abroad as migrant workers or migrant workers, because they were left long enough so that there is a trial. The third factor is that the husband cannot give birth or money for the needs of his wife and children so that his wife filed for divorce at the Dompu Religious Courts.